Pemilu Presiden Iran 2009 dan Upaya Destabilisasi Iran - Indriana Kartini (Jurnal Penelitian Politik, 2009)
Iran s 2009 presidential election became a big challenge for President Mahmud Ahmadinejad to preserve hispowerfor a second term The challenges were not only comefrom reformist groups but alsofrom conservative groups of which his political affiliation belong In addition international society also concerned with Ahmadinejad political statement andpolicy that could harm Iran national interests This paper will examine Iran s 2009 presidential election and the efforts offoreign forces to destabilize the Islamic Republic of Iran In this paper the electoral process including electoral competition between conservative and reformist groups and allegation offraud will be analyzed This paper will argue that tense competition between conservative and reformist groups in presidential elections has sharpened political division in Iran.